Interleukins, growth factors, and transcription factors are key targets for gene therapy in osteoarthritis: A scoping review - Uebelhoer, Melanie; Lambert, Cécile; Grisart, Juliane; Guse, Kilian; Plutizki, Stanislav; Henrotin, Yves (Frontiers in Medicine, 2023)
Objective: Osteoarthritis (OA) is the most common degenerative joint disease, characterized by a progressive loss of cartilage associated with synovitis and subchondral bone remodeling. There is however no treatment to cure or delay the progression of OA. The objective of this manuscript was to provide a scoping review of the preclinical and clinical studies reporting the effect of gene therapies for OA. Method: This review followed the JBI methodology and was reported in accordance with the PRISMA-ScR checklist. All research studies that explore in vitro, in vivo, or ex vivo gene therapies that follow a viral or non-viral gene therapy approach were considered. Only studies published in English were included in this review. There were no limitations to their date of publication, country of origin, or setting. Relevant publications were searched in Medline ALL (Ovid), Embase (Elsevier), and Scopus (Elsevier) in March 2023. Study selection and data charting were performed by two independent reviewers. Results: We found a total of 29 different targets for OA gene therapy, including studies examining interleukins, growth factors and receptors, transcription factors and other key targets. Most articles were on preclinical in vitro studies (32 articles) or in vivo animal models (39 articles), while 4 articles were on clinical trials related to the development of TissueGene-C (TG-C). Conclusion: In the absence of any DMOAD, gene therapy could be a highly promising treatment for OA, even though further development is required to bring more targets to the clinical stage.